A critical introduction to metadata for e–science and e–research. (6th February 2014) - Garoufallou, Emmanouel; Papatheodorou, Christos
Scientific research is moving towards multi–disciplinary, multi–institutional collaboration and therefore powerful tools and infrastructures based on interoperability principles are needed to support this trend. This paper introduces the special issue on the metadata for e–science and e–research of the International Journal on Metadata, Semantics and Ontologies. This special issue seeks to draw attention to the on–going challenges that scientists and systems developers face in the area of metadata and data management for e–science and e–research. In particular, the objectives of this special issue are (a) to present some of the latest research in this field, especially in relation to the use of metadata for addressing challenges associated with the management of scientific and research data across a broad range of applications; and (b) to highlight some of the challenges associated with the use of metadata, and encourage further research in this area. The special issue includes four papers reporting innovative approaches to key issues in the area of metadata for e–science and e–research, such as metadata modelling and standardisation, data quality and data re–use.